Sodium-doped lithium zirconate nano squares: synthesis, characterization and applications for CO2 sequestration - Khokhani, Mrinal; Khomane, Ramdas B.; Kulkarni, Bhaskar D. (Journal of Sol-Gel Science and Technology, 2012)
Nano squares of sodium-doped lithium zirconate have been synthesized by a simple citrate based sol-gel method at room temperature in the presence of cetyl trimethylammonium bromide (CTAB) as a surfactant. The structural and morphological properties were investigated by X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) respectively. XRD analysis of sample calcined at 900 A degrees C for 4 h shows the formation of monoclinic lithium zirconate phase. The TEM shows the interesting morphology of formation of nano squares of sodium doped lithium zirconate sample. The carbon dioxide sorption capacity was carried out by TGA analysis at different high temperatures. It is observed that the sample shows similar to 20 wt% carbon dioxide sorption at higher temperature (650 A degrees C) within 20 min which are better than the known reports.
Keywords: Carbon dioxide; CTAB; Lithium zirconate; Sodium doped lithium zirconate; sol-gel; TEM; XRD